Rescuing Sharia Bank’s Performance from Emerging Financing Risks Using Capital Adequacy - Pungky Lela Saputri; Mariam Binti Setapa; M Fatchurrohman; Muhammad Iqbal Ramadhani; Tika Mutiani (UPT Publikasi Ilmiah UNISBA, 2026)
This research investigates the impact of financing risk on the performance of Sharia banks in Indonesia, a critical issue given the increasing complexity of risk management in the Islamic banking sector. Specifically, it examines how Non-Performing Financing (NPF) affects Return on Assets (ROA) and evaluates whether the Capital Adequacy Ratio (CAR) can moderate this relationship. A quantitative approach was employed using Moderated Regression Analysis (MRA), with secondary data drawn from Indonesian Sharia banks registered with the Financial Services Authority (OJK) and consistently publishing financial statements from 2016 to 2022. The results indicate that NPF has a negative and significant effect on ROA. Meanwhile, CAR not only has a direct positive and significant effect on ROA but also plays a moderating role by mitigating the adverse impact of NPF on bank performance.